221k views
3 votes
If f(x)=x^2 and g(x)=1÷2x+3 find g(f(-1))

1 Answer

4 votes

ANSWER


g(f( - 1)) = (1)/(5 )

Step-by-step explanation

The given function is:


f(x) = {x}^(2)

and


g(x) = (1)/(2x + 3)


g(f(x)) = g( {x}^(2) )


g(f(x)) = \frac{1}{2{x}^(2) + 3 }

To find g(f(-1)), we substitute x=-1, to obtain;


g(f( - 1)) = \frac{1}{2{( - 1)}^(2) + 3 }

We simplify the square in the denominator to get,


g(f( - 1)) = (1)/(2+ 3 )

We now add the denominator to obtain;


g(f( - 1)) = (1)/(5 )

User Jonty Morris
by
5.9k points